CO2 gasification kinetics of Shenhua bituminous coal by isothermal thermogravimetric analysis. (19th September 2021) - Zhang, Jinzhi; Wang, Zhiqi; Zhao, Ruidong; Wu, Jinhu
Abstract: Gasification kinetic analysis of three Shenhua bituminous coal samples with various particle size ranges were carried out at three different temperatures (1000, 950, and 900°C) for 30 min using the gasifying agent of CO2 with the flow rate of 40 ml min −1 . The average particle sizes for sample A, sample B, and sample C were 43.4, 168, and 293 μm, respectively. Experimental results indicated that there were differences among the weight loss curves of three coal samples with different particle sizes. Furthermore, the differences became larger with the decrease of temperatures. Among the 11 used reaction mechanisms, two‐dimensional growth of nuclei following the Avrami‐Erofeev equation (A2) was proved to be the most appropriate one to fit the gasification data of Shenhua bituminous coal samples, as it can reconstruct gasification curves with high correlation coefficients (R 2 > 0.95). The calculated values of apparent activation energy ( E ) for sample A, sample B, and sample C were 95.9, 79.1, and 69.4 kJ mol −1, respectively. It was also found that the particle size had significant influence on kinetic data. The apparent activation energy decreased when there was an increase of the particle size. The compensation relationship of E and A (apparent pre‐exponential factor) was noted, and the fitted mathematic formula was ln A = 0.1041 E +0.540 28 (R 2 = 0.999).